ACC deaminase and IAA producing growth promoting bacteria from the rhizosphere soil of tropical rice plants. (17th May 2013) - Bal, Himadri Bhusan; Das, Subhasis; Dangar, Tushar K.; Adhya, Tapan K.
<x xml:space="preserve">Abstract</x> Beneficial plant‐associated bacteria play a key role in supporting and/or promoting plant growth and health. Plant growth promoting bacteria present in the rhizosphere of crop plants can directly affect plant metabolism or modulate phytohormone production or degradation. We isolated 355 bacteria from the rhizosphere of rice plants grown in the farmers' fields in the coastal rice field soil from five different locations of the Ganjam district of Odisha, India. Six bacteria producing both ACC deaminase (ranging from 603.94 to 1350.02 nmol α‐ketobutyrate mg−1 h−1) and indole acetic acid (IAA; ranging from 10.54 to 37.65 μM ml−1) in pure cultures were further identified using polyphasic taxonomy including BIOLOG(R), FAME analysis and the 16S rRNA gene sequencing. Phylogenetic analyses of the isolates resulted into five major clusters to include members of the genera Bacillus, Microbacterium, Methylophaga, Agromyces, and Paenibacillus. Seed inoculation of rice (cv. Naveen) by the six individual PGPR isolates had a considerable impact on different growth parameters including root elongation that was positively correlated with ACC deaminase activity and IAA production. The cultures also had other plant growth attributes including ammonia production and at least two isolates produced siderophores. Study indicates that presence of diverse rhizobacteria with effective growth‐promoting traits, in the rice rhizosphere, may be exploited for a sustainable crop management under field conditions.